2020
DOI: 10.1101/2020.07.23.200378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platinum resistance induces diverse evolutionary trajectories in high grade serous ovarian cancer

Abstract: Resistance to therapy is an enduring challenge in cancer care. Here we interrogate this critical unmet need using high grade serous ovarian cancer (HGSC) as a disease model. We have generated a unique panel of platinum-resistant HGSC models and shown that they share multiple transcriptomic features with relapsed human HGSC. Moreover, they evolve diverse in vivo phenotypes reflecting the human disease. We previously characterised copy number signatures in HGSC that correlate with patient survival and now provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Next, we evaluated liquidCNA on real data derived from in vitro mixtures of two paired high grade serous ovarian cancer (HGSOC) cell lines [29] (see Method and Table S1). HGSOC cells were ideally suited for this evaluation as high levels of chromosomal instability are a hallmark of the disease [30, 31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we evaluated liquidCNA on real data derived from in vitro mixtures of two paired high grade serous ovarian cancer (HGSOC) cell lines [29] (see Method and Table S1). HGSOC cells were ideally suited for this evaluation as high levels of chromosomal instability are a hallmark of the disease [30, 31].…”
Section: Resultsmentioning
confidence: 99%
“…We divided a population of OVCAR4 cells into two aliquots, and the first aliquot was untreated and classified as ‘sensitive’. In a process described in detail by Hoare et al [29], cells from the second aliquot were cultured so that they evolved resistance to platinum-containing chemotherapy and thus were termed ‘resistant’. In addition to the high SCNA burden inherited from the ancestral sensitive cell line, resistant cells acquired new SCNAs during the in vitro evolution of resistance (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human HGSC cell lines OVCAR4 and COV318 were obtained from Prof. Fran Balkwill (Barts Cancer Institute, UK). Platinum-resistant HGSC cell lines (Ov4Cis, Ov4Carbo and CovCis) were generated by serial culture in increasing concentrations of either cisplatin or carboplatin, as we described previously 13 and subsequently cultured in drug-free media. Cells were grown at 37°C in a humidified incubator with 95% air and 5% CO 2 in DMEM (Gibco) supplemented with 10% FBS (Gibco) and 1% penicillin/streptomycin (Gibco).…”
Section: Cell Culture and Platinum-resistant Cell Linesmentioning
confidence: 99%
“…Repurposing non-oncological drugs for clinical applications is an exciting and cost-effective strategy that can provide rapid clinical translation 12 . We have previously developed a unique panel of platinum-resistant cell lines and in vivo models and shown that they closely resemble the genetic, transcriptional and clinical features of human HGSC 13 . Using these novel cell lines, we employed a drug screening approach to identify hit drugs that could potentially reverse platinum resistance.…”
Section: Introductionmentioning
confidence: 99%